(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
:This article examines the role of game-based learning in expanding English vocabulary among language learners. Vocabulary acquisition is a fundamental component of language proficiency, and innovative teaching methods are increasingly being employed to enhance students’ engagement and learning outcomes. Game-based learning integrates educational content with interactive and enjoyable activities, creating a motivating environment for vocabulary development.